Norway, expedition crew member, Oskar Wisting at Ny-Ålesund - Ellsworth, Lincoln, 1880-1951 (1926)
"Ready for the Flight. Roald Amundsen and Oscar Wisting – Veterans of the South Pole." Caption taken from Amundsen, R., & Ellsworth, L. (1927). First crossing of the polar sea (pp. 176). Garden City, Doubleday. Amundson-Ellsworth Transpolar Flight at Spitzbergen, 1926, Oskar Wisting, Ellsworth Exhibit